2009
DOI: 10.1093/annonc/mdp255
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of health-related quality of life in cutaneous melanoma

Abstract: Melanoma can be considered an emerging chronic disease that may considerably affect patients’ lives. The authors systematically reviewed the available literature on health-related quality of life (HRQOL) and melanoma. Of reviews and the selected studies, reference lists were hand-searched. The quality of the eligible studies was appraised based on 14 previously published criteria. Of the 158 abstracts, 44 articles were appraised, resulting in 13 selected studies written in English (published between 2001 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 25 publications
6
119
0
4
Order By: Relevance
“…Whereas PD was associated with significant and clinically meaningful reductions in HRQoL and utility, patients in nonprogressed health states (including SD and partial or complete response) had stable HRQoL scores or experienced small -although not clinically meaningful -improvements in HRQoL. In contrast, studies have shown that treatment with chemotherapy often comes at the cost of decrements in HRQoL caused by side effects of therapy [40,41].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas PD was associated with significant and clinically meaningful reductions in HRQoL and utility, patients in nonprogressed health states (including SD and partial or complete response) had stable HRQoL scores or experienced small -although not clinically meaningful -improvements in HRQoL. In contrast, studies have shown that treatment with chemotherapy often comes at the cost of decrements in HRQoL caused by side effects of therapy [40,41].…”
Section: Discussionmentioning
confidence: 98%
“…HRQOL PROMs were rated according to pre-defined criteria (assessing study quality, quality of tool employed and the generalisability of outcomes) [3]. The score was adapted to ensure its relevance to diabetes-related foot disease [4] and an overall quality 'score' (range, 0-15) was assigned as a gross marker of fulfilment of the criteriawhere 0 represented poorest quality and 15 best quality.…”
Section: Methodsmentioning
confidence: 99%
“…Two systematic reviews have shown that one third of all melanoma patients exhibit clinically relevant distress, especially anxiety symptoms [652,653].…”
Section: Gcpmentioning
confidence: 99%
“…Patients experience a deterioration of QL around the time of primary diagnosis, disease progression, and during systemic therapy [504,513,518,652,660,668,674,675]. Predisposing factors regarding QL progression have been insufficiently validated, albeit some studies have indicated a negative correlation with female gender, preexisting depression, lower social status, and lack of coping [655,676].…”
Section: Quality Of Lifementioning
confidence: 99%